2019
DOI: 10.1371/journal.pone.0226426
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to generating political prioritization for adolescent sexual and reproductive health in Kenya: A qualitative study

Abstract: BackgroundDespite the high burden of adverse adolescent sexual and reproductive health (SRH) outcomes, it has remained a low political priority in Kenya. We examined factors that have shaped the lack of current political prioritization of adolescent SRH service provision.MethodsWe used the Shiffman and Smith policy framework consisting of four categories—actor power, ideas, political contexts, and issue characteristics—to analyse factors that have shaped political prioritization of adolescent SRH. We undertook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…stakeholderswas critical to gain political support for controversial issues such as SRH. 66 Negative framing of sensitive SRH issues could result in significant stigmatisation and affect the level of prioritisation. 67 In our study, while internal framing had demonstrated success in generating consensus on the importance and provision of OSCC and abortion services, both services did not seem to be included in other parts of the health planning process, including costing and budgeting, operational planning, and monitoring and evaluation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…stakeholderswas critical to gain political support for controversial issues such as SRH. 66 Negative framing of sensitive SRH issues could result in significant stigmatisation and affect the level of prioritisation. 67 In our study, while internal framing had demonstrated success in generating consensus on the importance and provision of OSCC and abortion services, both services did not seem to be included in other parts of the health planning process, including costing and budgeting, operational planning, and monitoring and evaluation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…stakeholders – was critical to gain political support for controversial issues such as SRH. 66 Negative framing of sensitive SRH issues could result in significant stigmatisation and affect the level of prioritisation. 67 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 31 This lack of political will, fuelled by partisan politics, often has its roots in traditional socio-cultural norms that hinder family planning and other pregnancy prevention interventions for adolescents. 32 33 The lack of political will led to inadequate government financial support for SRH programmes. The inadequacy of financial support worsened with the impact of COVID-19, which affected support from donor agencies who otherwise might have supported SRH programmes.…”
Section: Discussionmentioning
confidence: 99%
“…At the regional and national levels, ASRH has been considered a low priority among politicians and government, which reflects attitudes among political leaders and decision-makers in sub-Saharan Africa more broadly 30 31. This lack of political will, fuelled by partisan politics, often has its roots in traditional socio-cultural norms that hinder family planning and other pregnancy prevention interventions for adolescents 32 33. The lack of political will led to inadequate government financial support for SRH programmes.…”
Section: Discussionmentioning
confidence: 99%